A study of the reading performance and academic achievements of college students in the Albay Normal School, 1960-1961 - Lorenzo, Patria (Gregorio) 1929- (s.n.], 1962)
This is an investigation of the reading performance of the freshman, sophomore, junior and senior classes as compared with total group performance; the relationship between reading performance and academic achievement of the students in each instructional level; and the significance of the results in terms of the predictive value of the reading tests used. The three tests used were Diagnostic Reading Tests, High School Reading Test, and Standard Test Lessons in Reading.